Regulation of B Lymphocyte Development by Histone H2A Deubiquitinase BAP1 - Lin, Yun Hsiao; Liang, Yue; Wang, HanChen; Tung, Lin Tze; Förster, Michael; Subramani, Poorani Ganesh; Di Noia, Javier M.; Clare, Simon; Langlais, David; Nijnik, Anastasia (Frontiers in Immunology, 2021)
BAP1 is a deubiquitinase (DUB) of the Ubiquitin C-terminal Hydrolase (UCH) family that regulates gene expression and other cellular processes, via deubiquitination of histone H2AK119ub and other substrates. BAP1 is an important tumour suppressor in human, expressed and functional across many cell-types and tissues, including those of the immune system. B lymphocytes are the mediators of humoral immune response, however the role of BAP1 in B cell development and physiology remains poorly understood. Here we characterize a mouse line with a selective deletion of BAP1 within the B cell lineage (Bap1fl/fl mb1-Cre) and establish a cell intrinsic role of BAP1 in the regulation of B cell development. We demonstrate a depletion of large pre-B cells, transitional B cells, and mature B cells in Bap1fl/fl mb1-Cre mice. We characterize broad transcriptional changes in BAP1-deficient pre-B cells, map BAP1 binding across the genome, and analyze the effects of BAP1-loss on histone H2AK119ub levels and distribution. Overall, our work establishes a cell intrinsic role of BAP1 in B lymphocyte development, and suggests its contribution to the regulation of the transcriptional programs of cell cycle progression, via the deubiquitination of histone H2AK119ub.